Mobility-as-a-Service of Integrating Shared Micro-Mobility with Public Transit - Shaat, Hani (My University, 2025)
This thesis explores how the public transport provider can offer Mobility as a Service (MaaS) solutions that include shared micromobility such as shared e-scooters. The goal is to understand what users value in these kinds of offers and how pricing and features can be designed to attract more users to use MaaS, which supports more sustainable travel and reduce car use in the region. To investigate this, a stated preference survey was conducted to see how different parts of a MaaS bundle affect people’s willingness to choose it. The survey tested factors like price, free ride time, and free unlocks, and was divided into two types of travel situations: single tickets and monthly passes. Each respondent answered scenarios designed to simulate real travel decisions. The responses were analyzed using a multinomial logit model, which helped estimate the influence of each feature. The results show that people care most about ease and flexibility. For single ticket users, the most important feature was unlimited ride time. For monthly pass users, the ability to avoid repeated unlock fees was most appreciated. While price had some impact, convenience and simplicity mattered more. Based on these results, two MaaS bundle proposals are presented. One is a single ticket add on with some included shared e-scooter minutes, designed for occasional users or tourists. The other is a monthly pass that includes unlimited unlocks and a set number of ride minutes, aimed at regular commuters. These proposals are grounded in user preferences and are meant to guide Västtrafik in designing effective and user-friendly MaaS services.
Keywords: Mobility-as-a-Service; public transit integration; multimodal transport; shared e-scooters; micromobility